Influência da texturização a laser em ferramentas de metal duro revestidas na usinagem do aço ABNT 1050 - Suarez, Mauro Paipa (2012)
In metal machining one of the most important topic is the understanding of the chip formation process. Its analysis leads to the conclusion of how important is the phenomena involved during the generation of a new engineering surface. Since 1930 E. M. Trent, one of the most important researcher in metal cutting of all times, has encouraged the study of the tribological behaviour at the chip-tool interface. This has served as the mainspring towards technological improvements, such as the use of adequate cutting fluids and tool coatings more and more resistant, which aims to prolong tool lives. It is known from the surface engineering that different surface topographies present different tribological behaviour. The use of laser technology allows to alter the topography of the tool surfaces without affecting their mechanical properties. The main objective of the present work is to evaluate the influence of laser textured surfaces of coated cemented carbide cutting tools in the machinability of ABNT 1050 steel in turning operation. The tools were textured in three different stages, varying the texture geometry and the laser power over the rake face of triple coated (TiCN-Al2O3-TiN) cemented carbide tools. The textures were characterized by electronic interferometry and scanning electron microscopy (SEM). The machining tests were carried out in several cutting conditions (cutting speed and feed rate) and different lubri-cooling atmospheres (dry, MQL and flood cooling). The machinability was evaluated also in three different classificatory stages. In the first stage (using the same texture geometry and different laser parameters) the machining force components and the workpiece surface roughness were considered as the evaluating parameters. In the second stage (different texture geometry) only the machining force components were considered. Finally, in the third stage (using the best texture determined by the previous stages) the tool life was the evaluating parameter. The results showed that from the machinability evaluating parameters, only the tool life with flood cooling presented positive response of the laser texture on the tool rake face. Under the other two lubri-cooling atmospheres (dry and MQL) the results did not show significant differences in the behaviour of the evaluating parameters. Varying the cutting conditions did not modify these results. This work has thus contributed for the study of the laser-materia interaction showing that this new technology of tool texturing is viable and can improve tool lives and hence shop floor productivity.